2021
DOI: 10.1002/pol.20210406
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on the structure–properties relationship of multiblock copolymers

Abstract: Multiblock copolymers represent a fascinating class of materials that sits at the very heart of industrial applications and fundamental polymer science. They are most often made of a linear succession of incompatible “soft” and “hard” segments that microphase separate at room temperature while they can be easily re‐homogenized upon heating. This thermoreversible character provides them with decisive advantages with respect to other rubber‐based materials such as vulcanized elastomers, making them indispensable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 186 publications
(386 reference statements)
2
26
0
Order By: Relevance
“…Thermoplastic copolyesters (TPCs) constitute a materials class with commercial relevance, employed in demanding engineering applications 30 where the combination of thermal stability, chemical and abrasion resistance, and mechanical strength are critical. The molecular microstructure is described by the alternation of immiscible hard and soft segments (i.e., blocks) linked with ester bonds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thermoplastic copolyesters (TPCs) constitute a materials class with commercial relevance, employed in demanding engineering applications 30 where the combination of thermal stability, chemical and abrasion resistance, and mechanical strength are critical. The molecular microstructure is described by the alternation of immiscible hard and soft segments (i.e., blocks) linked with ester bonds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One of the most well-known examples is a block copolymer consisting of chemically distinct chains . It has been widely recognized that an AB diblock copolymer can spontaneously form diverse ordered structures simply by tuning the composition and interaction. , Introducing additional blocks greatly increases the molecular complexity and offers extra handles to regulate phase formation and transition. Precise manipulation of molecular parameters such as the block sequence, regio-configuration, chain architecture, and molecular symmetry provides alluring opportunities to generate exquisite structures and achieve advanced properties. , For example, it has been recently demonstrated that rationally adjusting the relative block length of multiblock copolymers affords access to rich unconventional phases otherwise unattainable. …”
Section: Introductionmentioning
confidence: 99%
“…5−8 Precise manipulation of molecular parameters such as the block sequence, regioconfiguration, chain architecture, and molecular symmetry provides alluring opportunities to generate exquisite structures and achieve advanced properties. 9,10 For example, it has been recently demonstrated that rationally adjusting the relative block length of multiblock copolymers affords access to rich unconventional phases otherwise unattainable. 11−16 The vastly expanding design space of multiblock copolymers, however, is both an opportunity and a challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2,3 The properties can therefore be tuned by preparing products with different relative block lengths and different block sequences. 4,5 However, each individual target composition typically requires a separate synthesis, which can be quite elaborate depending on the architecture. [6][7][8][9] This is nearly always carried out in batch reactions with each block made sequentially, which is especially necessary with mechanistically incommensurate monomers/repeating units.…”
Section: Introductionmentioning
confidence: 99%